2006
DOI: 10.1016/j.otohns.2006.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Adult Spontaneous CSF Otorrhea: Correlation with Radiographic Empty Sella

Abstract: C-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 18 publications
8
80
0
7
Order By: Relevance
“…[19][20][21] This caused a decrease in CSF reabsorption due to a diminished pressure gradient between the intracranial pressure and the venous sinuses through the arachnoid granulations. 15,18,20,24,25 In our case, the intravenous increase in pressure was not due to stenosis or occlusion of a major venous sinus, as it is not infrequently seen in association with AVMs. Intracranial pressure increased to match increase in cerebral sinus venous pressure and re-establish the normal gradient.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…[19][20][21] This caused a decrease in CSF reabsorption due to a diminished pressure gradient between the intracranial pressure and the venous sinuses through the arachnoid granulations. 15,18,20,24,25 In our case, the intravenous increase in pressure was not due to stenosis or occlusion of a major venous sinus, as it is not infrequently seen in association with AVMs. Intracranial pressure increased to match increase in cerebral sinus venous pressure and re-establish the normal gradient.…”
Section: Discussionmentioning
confidence: 51%
“…Intracranial pressure increased to match increase in cerebral sinus venous pressure and re-establish the normal gradient. 20,25 Two theories are most prevalent in explaining the etiology of these spontaneous, non-traumatic, CSF fistulas. The first involves the presence of a congenital defect which can give rise to a CSF leak.…”
Section: Discussionmentioning
confidence: 99%
“…Prichard et al [9] noted that five of seven patients with spontaneous CSF otorrhoea had an empty or partially empty sella, that is, an increased pressure in the sella turcica caused the pituitary gland to flatten out along the interior walls of the sella turcica cavity. Consequently, the authors have suggested that if spontaneous CSF otorrhoea is evident or TTD is diagnosed, it is important to rule out in- creased intracranial pressure [9] . In another report, Hadi et al [10] noted that 13 of 23 patients with TTD had semicircular canal dehiscence.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, si agrupamos los pacientes con fístulas espontáneas, la incidencia de STVP es del 63% -100% de los casos 78,82,84 , considerando la silla vacía en sus diferentes grados.…”
Section: Diagnóstico De La Rinorrea En La Stvpunclassified
“…La mala "compliance" intraselar para amortiguar la onda sistólica del lcr en los casos de diafragma incompetente 26,27 y/o una hipertensión intracraneal crónica oculta 65,70,81 o manifiesta 55,97 , puede finalmente erosionar el débil suelo de la silla turca u otro punto débil de la base de cráneo 78,81,84,97 y provocar una rinorrea. Shetty y col 84 , publicaron 11 pacientes con fístulas a nivel de las paredes antero-laterales del seno esfenoidal, la mayoría en la zona de unión con el suelo de la fosa media, comparándolos con un grupo control de 100 personas normales.…”
Section: Fístula De Líquido Cefalorraquídeounclassified